Mycobacterium abscessus Infections in Solid Organ Transplant Recipients: Single-Center Experience in the United States, 2013–2018. (18th May 2022) - Ebisu, Yosuke; Natori, Yoichiro; Rosello, Gemma; Anjan, Shweta; Simkins, Jacques; Camargo, Jose F; Morris, Michele I; Martinez, Octavio V; Abbo, Lilian M
Abstract: Background: Mycobacterium abscessus is increasingly recognized as a human pathogen causing life-threatening infections in immunocompromised patients. There is a paucity of data around this topic in solid organ transplant (SOT) recipients. Methods: This work was a single-center retrospective cohort study of all SOT recipients with a positive culture for M abscessus between 2013 and 2018. Results: A total of 20 patients (55% female) met inclusion criteria, including 1 kidney recipient (5.0%), 2 liver recipients (10.0%), 12 lung recipients (60.0%), 1 heart recipient (5.0%), and 4 combined organ recipients (20.0%). The median time from SOT to infection was 100 days (range, 30–431 days). Thirteen (65.0%) patients (1 kidney, 1 heart, 7 lung, 1 liver, 1 intestine, and 2 multivisceral) were treated with a median duration of 185 antibiotic days (range, 20–523 days). Among them, M abscessus was isolated from respiratory samples in 8 and nonrespiratory samples in 5; 4 of 13 (30.8%) patients had treatment failure and 3 of 13 (23.1%) had unrelated deaths within 1 year after diagnosis. Seven patients (5 lung transplant recipients) with the organism isolated from respiratory samples were not treated as their cultures represented airway colonization or contamination; of those, 2 (28.6%) died (unrelated to infection) and 5 (71.4%) were alive without the infection after 1 year of follow-up. Conclusions: Mycobacterium abscessus infections affect SOT recipients with a high proportion of clinical failures. However, in lung recipients, not all positive cultures correlated with infection, and without treatment some patients had good clinical outcomes. Thus, differentiating colonization from infection is important, and infection prevention measures and novel therapeutic agents are needed for SOT recipients. Abstract : Mycobacterium abscessus causes serious infection in solid organ transplant recipients; hence, infection control and effective treatment options are needed. In lung transplant recipients, culture positivity in respiratory samples does not always mean active infection, and balanced decisions should be made for initiating treatment.